Nine new species and new records of euryglossiform Scrapter Lepeletier & Serville (Hymenoptera: Colletidae) from South Africa - Kuhlmann, Michael; Friehs, Thyra (European Journal of Taxonomy, 2020)
Nine new species of the South African endemic group of euryglossiform bees of the genus Scrapter Lepeletier & Serville, 1828 are described, thus bringing the total number of species to 29 in this species-group: Scrapter avontuurensis Kuhlmann sp. nov. ♀, S. bokkeveldensis Kuhlmann sp. nov. ♀, S. fynbosensis Kuhlmann sp. nov. ♀, S. hergi Kuhlmann sp. nov. ♂, S. keiskiensis Kuhlmann sp. nov. ♀, S. mellonholgeri Kuhlmann sp. nov. ♀♂, S. nitens Kuhlmann sp. nov. ♀, S. oubergensis Kuhlmann sp. nov. ♀ and S. willemstrydomi Kuhlmann sp. nov. ♂. The new replacement name S. punctulatus nom. nov. is proposed for S. punctatus Kuhlmann, 2014 which is a junior primary homonym of S. punctatus Lepeletier & Audinet-Serville, 1825 (= Allodape punctata [Lepeletier & Audinet-Serville, 1825]). Moreover, new records for already described taxa are presented and an updated key to all species of euryglossiform Scrapter is provided.